Association of Glycated Haemoglobin levels, LDL levels, Systolic blood pressure, and BMI with carotid artery intima-media thickness (CIMT) in patients with type 2 diabetes mellitus - Purwito, Muh Arss Budi; Wajib, Yuyun Yueniwati; Arisetijono, Eko; Andarini, Sri (Journal Of Cardiovascular, Neurovascular & Stroke, 2022)
Background : Glycated haemoglobin in type 2 diabetes mellitus (DM) patients together with other modifiable major risk factors are potentially increase oxidative stress and decreasing nitric oxide activity which triggers atherosclerosis. Atheroslerosis can be detected using B-mode ultrasound to measure carotid artery intima-media thickness (CIMT). The aim of this study is to analyze the association between glycated haemoglobin levels (Hb A1c), LDL levels, systolic blood pressure (SBP), and BMI to CIMT in type 2 DM patients. Methods : This was an observational analytic study with a cross-sectional approach. There were 30 study subjects from Endocrine Clinic at Saiful Anwar Hospital, Malang, Started in September 2018 to December 2019. The subjects were examined using B-mode ultrasound for CIMT measurement, as well as examination to evaluate Hb A1c levels, LDL levels of SBP and BMI. All collected data were statistically analyzed. Results : The correlation between CIMT and Hb-A1c satitistically shows significant association (P = 0.015) with negative correlation coefficient (P = - 0.441), while others variable showed insignificant result. The linear regression between Hb-A1c and CIMT showed 18.3% effectiveness. Conclusion : There was a significant association in the predictor variable levels of Hb-A1C and CIMT with inverse corellation with effectiveness 18.3%